First experience with BAK-free travoprost 0.004% in topical glaucoma medication - Gado, Ahmed Salah (Dove Medical Press, 2012)
OBJECTIVES: Benzalkonium chloride (BAK)-free travoprost 0.004% (Travatan Z(®), Alcon Laboratories, Inc, Fort Worth, TX) is a new formulation that was developed with the aim of creating a formulation of travoprost that would maintain the intraocular pressure (IOP)-lowering efficacy and have an improved overall safety profile, particularly improved ocular surface tolerability. METHODS: Thirty newly diagnosed primary open-angle glaucoma (POAG) patients were treated with BAK-free travoprost 0.004%. IOP readings were recorded at baseline before initiating treatment, at 4–6 weeks, and after 12 weeks of starting treatment. In addition, patient demographics, subjective symptoms (ie, burning, foreign-body sensation, itching, and stinging), and objective clinical signs such as conjunctival hyperemia were collected. Subjective symptoms were evaluated using a four-point scale ranging from “no symptoms,” “mild symptoms,” “moderate symptoms” to “severe symptoms.” As for clinical signs, severity of conjunctival hyperemia was evaluated. All other adverse events were collected. RESULTS: BAK-free travoprost 0.004% provided an IOP decrease in all patients, with an overall mean of 28.3 ± 2.1 mmHg at baseline to a mean of 18.7 ± 1.6 mmHg at 4–6 weeks, and a mean of 18.4 ± 1.4 mmHg after 12 weeks. Both subjective symptoms and objective clinical signs were very few after treatment. CONCLUSION: The results demonstrate that BAK-free travoprost 0.004% is an effective, well tolerated, and safe medication in POAG patients.